Dynamic Panel Analysis of Influence of Quality of Human Capital on Total Factor Productivity in Old European Union Countries - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2016)
Improving productivity is the main determinant of long term develop-ment. In the EU in Europe 2020 strategy special attention was given to the role of quality of human capital (QHC) as an important determinant of productivity growth. In this context the aim of the article is to assess the impact of the QHC on total factor productivity (TFP) in 'old' EU countries. The research is conducted at macroeconomic level. EU economies must build their competitiveness in reality of knowledge-based economy. Thus, the QHC was analysed from the point of view of global knowledge economy. This factor was treated as a multidimensional phenom-enon. As a result, it was measured with application of TOPSIS method, which al-lowed to obtained time series for dynamic panel analysis of determinants of TFP. In order to evaluate TFP parameters of the Cobb-Douglas production function for de-veloped EU countries were estimated. Then, the relationship between the QHC and the level of TFP was assessed with application of dynamic panel model. The re-search was based on Eurostat data for the years 2000-2010. It confirmed a signifi-cant influence of the QHC on the level of TFP in the analysed economies.
Keywords: O47; C23; C38; 330; panel model; TOPSIS; TFP; quality of human capital; EU countries